Camellia sinensis leaf extracts lacking catechins exert depigmentary effects through ERK-dependent, MiTF-mediated tyrosinase downregulation in melan-a cells and a human skin equivalent - Kim, Donghyun; Park, Nok Hyun; Hwang, Jeong Ah; Kim, Jeongkee; Na, Yong-Joo; Hwang, Jae Sung; Lee, Chang Seok; Yang, Deok Chun (Archives of Biological Sciences, 2019)
Paper description: Green tea (Camelia sinensis) polyphenol catechins have been studied extensively for their health benefits and for their anti-melanogenic properties. Bioactive components such as polysaccharides, amino acids and lipids have received little attention. We examined the anti-melanogenic properties of tea leaf extract, which is mostly comprised of polysaccharides. We describe the anti-melanogenesis mechanism by melan-a cells and a human skin equivalent. The fraction of tea extract without catechins regulates melanin synthesis by ERK-dependent degradation of MiTF and subsequent downregulation of tyrosinase expression. C. sinensis leaf extracts without catechins could be developed as a new skin-lightening agent. Abstract: Green tea from Camellia sinensis, a popular beverage worldwide, is also considered a herbal medicine. The bioactive compounds of green tea include polyphenols, polysaccharides, amino acids, and vitamins. Tea polyphenols are composed of various catechins such as epigallocatechin-3-gallate (EGCG), whereas polysaccharides include complex pectic substances and glycoproteins. Unfractionated C. sinensis leaf extracts show various pharmacological effects that are attributable to catechins, which include antimelanogenic properties. Most studies have focused on the biological function of catechins in green tea, and the effects of C. sinensis leaf extracts lacking catechins (CSLE-LC) have received little research attention. We examined the skin-whitening properties of the fraction lacking catechins. The melanin content in melan-a cells was significantly reduced, as has been shown for unfractionated C. sinensis extracts and catechins. We also elucidated the molecular mechanism underlying the antimelanogenic effects of CSLE-LC on skin melanocytes. Our results show that CSLE-LC acts through inhibition of MiTF and subsequent activation of extracellular-signal regulated kinase (ERK) to reduce tyrosinase protein levels. We confirmed the whitening ability of CSLE-LC using a human skin equivalent. Our findings provide the first evidence that CSLE-LC could exert efficient antimelanogenesis activity, and suggest that polysaccharides as well as catechins contribute to the whitening efficacy of C. sinensis leaf extracts. https://doi.org/10.2298/ABS190510031K Received: May 10, 2019; Revised: May 23, 2019; Accepted: May 24, 2019; Published online: May 28, 2019 How to cite this article: Kim D, Park NH, Hwang JA, Kim J, Na YJ, Hwang JS, Lee CS, Yang DC. Camellia sinensis leaf extracts lacking catechins exert depigmentary effects through ERK-dependent, MiTF-mediated tyrosinase downregulationin melan-a cells and a human skin equivalent. Arch boil Sci. 2019;71(3):483-8.